HISTORICAL REVIEW OF NEUROPHYSIOLOGICAL MECHANISMS OF MENTAL PROCESSES - Papoyan, V. R. (Modern Psychology, 2018)
The article is dedicated to finding out the connections between neurophysiological processes and such mental functions, as: motivation of behavior, associations, connected with cognitive processes, problems of neurophysiological mechanisms of different origins of switching, which are in the basis of some psychic processes. Main principles of psychology, which represent methodological fundament of psychology and are based on the achievements of natural sciences, provide the exploration of the mechanisms. Analysis of explorational and theoretical researches of E. Hasratyan, which provided the discovery of neurophysiological and general basics of some mental processes, remains significantly important. They are directed to defining and understanding deeper neurophysiological processes, which explain their connection to mental functions.
Keywords: neurophysiology, mental processes, switching, motivation, behavior, reflex.